Analysis of the functional performance of different mortars with incorporated residues. (May 2020) - Matias, Gina; Torres, Isabel; Rei, Filipe; Gomes, Filipe
Abstract: Mortars provide protection to constructive elements and contribute significantly to thermal and acoustic comfort of the indoor environment. Taking into account the technical and ecological requirements of the mortars industries, it is fundamental to use more recycled or natural raw materials, and products with lower environmental impact. Also, the development of multifunctional mortars suited for different substrates ensures more versatility of the products. Looking to address these issues, this paper presents the development of mortars incorporating several different by-products: cork, glass and rubber. For this purpose, mortars with these three by-products were developed and improved to obtain optimized compositions. Thermal and acoustic behaviour were analysed and fire reaction was also tested. These mortars were also applied in exterior walls and its physical and mechanical behaviour was analysed. Very promising results were obtained. It was possible to fit these mortars into the specification standard for CE marking of mortars for rendering and plastering. Highlights: The development of multifunctional mortars for eco-friendly construction represents an important achievement. Technical multifunctional mortars might allow reducing energetic consumption and increase the durability. The use of by-products might improve mortars thermal and acoustic behaviour. Multifunctional mortars will meet the needs of several different markets.